Submerged Floating Tunnel Bridge (SFTB): A Status Report and Evaluation of Technology Readiness Level (TRL) - Nurcahya Nugraha; Jamiatul Akmal; Asnawi Lubis (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2022)
One of the problems in archipelagic countries is the land transportation system that has not been integrated between islands. In a relatively wide strait and with a high level of depth, it is impossible to build a bridge. In this case, a submerged floating tunnel bridge/SFTB would be an effective choice. SFTB is an underwater tunnel transport route submerged between the seabed and the surface. Known as the